The Role and Challenges of Guidance Counselors in Inclusive Education - Marizki, Fanesa; Damayanti, Rika; Masya, Hardiyansyah (Yayasan Ilomata, 2025)
Inclusive education has received much attention globally in relation to ensuring equal opportunities in learning for all students with diverse special needs. This systematic review explores the roles and challenges of counseling teachers in inclusive education through an analysis of 21 research articles. The results show that counseling teachers play an important role in emotional and academic support, development of individualized education plans, collaboration among stakeholders, and crisis management in an inclusive environment. Inadequate training, limited resources, heavy caseloads and systemic barriers hinder their implementation. Bk teachers identified targeted professional development, integration of assistive technology, and improved policies and resources as prerequisites to overcome these challenges. The current study demonstrates the importance of holistic and interdisciplinary methods to empower counseling teachers in building the supportive platforms needed to develop inclusive practices. Its findings add to actionable strategies and policy developments that can be established to improve inclusive education systems worldwide.